Should the allegedly called animal rights be taken seriously? : an analysis based on the approach of Martha Nussbaum (Prudentia Iuris, 2017)
This work starts from the premise that it is difficult for iusnaturalism to take seriously the arguments about the animal rights and that this is, partly, due to its understanding of man, law and justice. It will be explored the possibility that this approach may result insufficient to take care of the ethical-juridical problematic that the contemporary man perceives - increasingly and with great interest - under the topic “animal rights”. The subject will be analyzed, based on the contributions of Martha Nussbaum, a model that appears as overrun of both the animalist approaches, as well as the ecologists. There is an exposition of these models, followed by the Nussbaum approach and its extension to the topic under discussion, finally a critical evaluation of their contributions, especially of the Notions of dignity and justice underlying it.
Keywords: Animal rights; Nussbaum; Dignity; Justice; Iusnaturalism